المكـان في روايـات سـحر خليفـة - الشّـامي حسّـان; أحمـد لاريسّــا (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
حظي المكان الروائي باهتمام الروائيين في العصر الحديث ، باعتباره الرابط بين جميع عناصر الرواية ، فهو مسرح الأحداث، والمجال المادي الذي تتحرك فيه الشخصيات، وتجري ضمنه كل الصراعات، وبذلك شغل المكان بأنماطه المختلفة الدراسات الحديثة، فاهتمت بعلاقة المكان بالمكونات الروائية كافة، وبخاصة الشخصية، وأثر هذه العلاقة في تشكيل المكان، ومنحه سمات ومعالم محددة ، تبعاً لمسار القضية، وحركة الواقع الفلسطيني . وقد شكلت علاقة الشخصية بالمكان أهمية كبيرة نظراً للعلاقة التبادلية بينهما، حتى غدا المكان في بعض الروايات منطلقاً للأحداث ، وغاية لوجود الشخصيات ، وتأكيد هويتها ووجودها. يتناول هذا البحث المكان في روايات الكاتبة سحر خليفة ، فيبين دوره في تجسيد الواقع الفلسطيني، وأهميته في حياة الشخصية الفلسطينية، كما يظهر دور الوصف في إبراز تضاريسه وأبعاده الدلالية. The setting in novels has captured the novelists’ attention in the contemporary literary world. It was considered the link between elements of the novel. It is، after all، the setting of the events، the substantial scope in which characters move and where all conflicts take place. Thus، the setting، with its different types، has preoccupied modern studies which examined the relation between the setting and the narrative elements، especially the character. Studies have preserved to reflect the relation between setting and character and the effect this relation has on forming the setting and giving it specific characteristics depending upon the case and the reality of the Palestinian movement. This relation between setting and character has acquired much importance due to the mutual relation between the two، to the extent that setting، in some novels، has become a basis for the events، a purpose for forming characters، and a conformation for their identity and existence. This research sheds light on setting in SaharKhalife’s novels، its role in personifying the Palestinian reality، and studying its importance in the life of the Palestinian character، in addition to showing the role of description in projecting its indicative features and dimensions.